PENGARUH PENGENAAN PAJAK PERTAMBAHAN NILAI DAN CUKAI ROKOK TERHADAP SKEMA FINANSIAL PRODUK ROKOK PADA KANTOR BEA DAN CUKAI KUDUS (Students' Journal of Accounting and Banking, 2013)
This study is aimed at: (1) Determine the influence of cigarette tax to the selling price per unit that has been determined by the company, (2) Determine the magnitude of the influence of cigarette tax on sales income of the company, (3) determine the effect of VAT on the selling price per unit that has been determined by the company, (4) Knowing how VAT may affect the company's sales income. This study is quantitative research. The populations are 14 tobacco companies that are listed in the Customs Office in Kudus. Normality test, the classical assumption, regression analysis, t test, F test and the coefficient of determination are used to analyze data. SPSS for windows is used to calculate data. The results show that: (1) There is a positive effect on the price per unit excise tax, this means that any increase in excise duty will increase the price per unit and any excise reduction will lower the price per unit, (2) There is a positive effect of the VAT to the price per unit, this means that any increase in VAT will increase the price per unit and any reduction in VAT would lower the price per unit, (3) There is a positive effect on the sales tax, this means that any increase in excise duty will increase sales and any reduction would lower the sales tax and (4 ) There is a positive effect of VAT on sales, this means that any increase in VAT will increase sales and any VAT reduction will reduce sales.Keywords: Cigarette, Value Added Tax, and Sales